Scientometrics in the Library as a Research Support Tool in the Ural Branch of the Russian Academy of Sciences - Yu. D. Prokof’eva (Библиосфера, 2022)
Scientometrics today is an effective tool to analyze and evaluate the activities of scientific organizations, as well as to form strategies and forecasts for the development of scientific research. To carry out scientometric research, specialists are required with the knowledge and skills to work with scientometric data. Such specialists can be employees of research libraries. The purpose of the study is to determine the role of the research library in carrying out scientometric works in the interests of research organizations. The article describes the experience of bibliometric analysis and the development of scientometrics in the Central Scientific Library of the Ural Branch of the Russian Academy of Sciences (UB RAS). The study of the state of scientometrics in research organizations of UD RAS was carried out by the method of questionnaires. As a result, it is revealed that most often work in scientometric databases is carried out by scientific secretaries and deputy directors for scientific work. In some answers one can see a limited use of scientometric databases capabilities. Thus, the need for a specialist in scientometrics has been identified. Despite the indicated advantages of library specialists, the importance of interaction between a research organization and a library is emphasized for conducting a high-quality scientometric analysis.